Analysis of the Constructive Features of the Earth Dam - Balzannikov Mikhail (MATEC Web of Conferences, 2018)
The article considers the earth dam of the run-of-river unit – Kuibyshev hydroelectric power station on the Volga river (Russia). The main parameters of the earth dam, peculiarities of its erection and operation are described. The article notes the importance of ensuring a high degree of reliability of water structures constructed near major cities. It is especially important to monitor the condition of retaining structures with long service life. The factors influencing the change of the initial design conditions of operation of the Kuibyshev run-of-river unit dam are discussed. The results of examination of the geometric parameters of the body of the dam, performed at different periods of its maintenance, are analyzed. Examination results revealed significant deviations of the elevation marks of the earth dam surface on the upstream side from the design values. Possible causes of the discrepancy between these parameters and the design solutions are considered. The conclusion is drawn that the most likely reason for these features of the dam design lies in the initial incompleteness of construction. The measures for carrying out repair work to improve the reliability of the earth dam are being recommended.